Peak Level of Pain while uprighting Molars with Tri-helical Uprighting Spring - Yadav, Rajiv; Lim, Dennis C (Orthodontic Journal of Nepal, 2016)
Introduction: Orthodontic treatment has clear positive effects on a patient’s physiological, functional, esthetic, psychological, and social health. However the most common and problematic sequel of orthodontic treatment is pain and discomfort. Objectives: To find out exact time of peak level of pain while uprighting molars for a week time with loop uprighting mechanics and weather the pain was associated with intake of pain medication. Materials & Method: A cross-sectional analytical study was performed on finally selected thirty orthodontic patients with uprighting molars with age range of 10-40 years from of the Department of Orthodontics, University of the East, Philippines. Digitest Electricpulp tester was used to calibrate subjects with similar pain threshold level. An optimal molar uprighting force of 100 grams was employed with a customized tri-helical molar uprighting springs made with 0.016X0.022” stainless steel archwire. Measurement was done using tension gauge. Simultaneously 12 thermometer pain scale and 6 questionnaires forms were given to the subjects which were to be completed within 7 days based on their pain perception. The data were analyzed with Wilcoxon rank sum test, Chi-square test. Result: Maximum pain was felt on day-1 during evening at 9:40 pm, which was strongly associated with intake of pain medication on day-1 with gradual decrease over a period of week. Conclusion: There is a great need of precautionary measures like pain medication to avoid disturbance from daily activities of patients undergoing orthodontic treatment.